Internal Senses in Nicholas of Cusa’ Psychology - Fiamma, Andrea (Revista Española de Filosofía Medieval, 2020)
The paper considers the Nicholas of Cusa’ interpretation of Aristotle’ De anima with regard to the functioning of the internal senses in the knowing process: sensus communis, vis memorialis, vis aestimativa, phantasia, vis imaginativa. The not numerous references on the Aristotelian doctrine of the internal senses in Nicholas of Cusa' work are organized, for the first time in the recent historiography on medieval theory of knowledge, in a systematic and ordered philosophical reconstruction.